2022
DOI: 10.3389/fnana.2022.940993
|View full text |Cite
|
Sign up to set email alerts
|

A combined use of silver pretreatment and impregnation with consequent Nissl staining for cortex and striatum architectonics study

Abstract: Despite a rapid growth in the application of modern techniques for visualization studies in life sciences, the classical methods of histological examination are yet to be outdated. Herein, we introduce a new approach that involves combining silver nitrate pretreatment and impregnation with consequent Nissl (cresyl violet) staining for cortex and striatum architectonics study on the same microscopy slide. The developed approach of hybrid staining provides a high-quality visualization of cellular and subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In order to further identify the bacterial-meningitis-induced brain damage caused by NMEC, we performed a histological examination involving Nissl staining to assess neuronal loss [ 13 ]. More shrunken neurons with pyknotic nuclei were found in NMEC-infected mice compared with mice that received PBS ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further identify the bacterial-meningitis-induced brain damage caused by NMEC, we performed a histological examination involving Nissl staining to assess neuronal loss [ 13 ]. More shrunken neurons with pyknotic nuclei were found in NMEC-infected mice compared with mice that received PBS ( Figure 4 a).…”
Section: Resultsmentioning
confidence: 99%
“…The results of HE staining showed that as the Cy dose increased, the cells in the hippocampal CA1 area exhibited vacuolization and pyknosis, their arrangement was disordered, and they were lost, with the high-dose exposure group showing the most marked changes, which further indicated that Cy exposure seriously disrupted the morphology of the rat hippocampus. To further observe neuronal damage, Nissl staining was used to assess the distribution and morphology of Nissl bodies [ 30 ]. The Nissl bodies are the main structures responsible for protein synthesis and can balance the levels of various neurotransmitters in the brain and maintain the stability of neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hippocampal sections were prepared from paraffin-embedded rat brain tissues using a slicer (RM2235, Leica, Germany). Next, the sections were routinely dewaxed in water, and Nissl staining was conducted in accordance with the standard protocol [23,24]. Finally, the sections were sealed with neutral balsam, imaged with Pannoramic DESK NanoZoomer S60 (C13210-01, HAMAMATSU, Co., Ltd.), and analyzed.…”
Section: Mwm Testmentioning
confidence: 99%